La polis grecque classique - Flore Lerosier (Frontière·s)
The study of the Greek colonial polis (city) is old and characterized by a dichotomy between city (astu) and countryside (chôra). This separation is now challenged with the consideration of the suburban space, the proasteion. It’s, indeed, a transitional space between town and countryside that makes more porous the city’s limits than the wall suggests and brings new elements to the study of the polis. Hence, it seems today that, for a Greek city, every space can’t be approached alone, without linking it to the others, whether these links are topographical, social, economic, political or religious.This article aims to study the consideration of the suburban space in the definition of the polis of Neapolis, founded at the end of the 6th century BC in Campania by Cumaeans and inhabitants of Parthenope. This polis is founded as the canonic model of the polis, while presenting these own characteristics. Indeed, it’s founded at the boundaries of the cumaean chora and seems to don’t have territory until 421 BC, capture of Cumae by Campanians. Furthermore, it’s installed next to an ancient establishment, Parthenope, became Palepolis and second pole of the polis, who was already using the port in piazza Municipio and, undoubtedly, a sacred area in piazza Nicola Amore.